Acute spontaneous intracerebral haemorrhage: treatment and management. (2nd June 2022) - Mc Lernon, Siobhan; Nash, Philip S; Werring, David
Abstract : Acute spontaneous intracerebral haemorrhage is a devastating form of stroke, with high rates of mortality and disability in survivors. Despite the burden of intracerebral haemorrhage, there remain few effective treatments that improve the patient outcome when compared to ischaemic stroke. Nonetheless, patients still benefit from specialist stroke unit care, including early interventions to prevent complications. Therapeutic nihilism should be avoided during the acute phase, as well as early care limitations. A proactive multi-targeted approach based on therapeutic strategies to prevent early haematoma expansion and attenuation of secondary brain injury are likely to be important in improving patient outcomes.